Zonasi, Kuota dan Rasionalisasi: Paradoks Implementasi Kebijakan Penataan Minimarket di Kabupaten Ciamis - Kokom Komariah; Utang Suwaryo; Neneng Yani Yuningsih (Universitas Negeri Medan, 2020)
This article aims to discuss the implementation of minimarket structuring policies in Ciamis Regency, West Java, in 2018. The problem is focused on policies regarding the zoning, allocation and quota of minimarkets in the administrative area of Ciamis Regency. To discuss this problem, a reference to the theory of policy implementation by Charles O. Jones (1996) is used. Data collected through in-depth interviews, observation and literature review and document review and analyzed qualitatively. This study concludes that the implementation of minimarket structuring policies in Ciamis Regency is paradoxical to the agenda and policy adoption partly because there are ten minimarkets operating without permits, misuse of business licenses and establishment of minimarket quotas that are not in line with efforts to foster entrepreneurship, fair business competition and improving regional economy.